Involvement that makes an impact on healthcare: Perceptions of the Swedish public. Issue 4 (June 2018) - Fredriksson, Mio; Eriksson, Max; Tritter, Jonathan Q.
Aim: 'Participation and influence in society' is the first of 11 objective domains in Swedish public health policy. The aim of this article is to investigate the views of the Swedish general population on the impact of a range of health participation activities, and whether these views were associated with sociodemographic characteristics. Methods: The study utilizes a national representative survey of the Swedish population, aged 15 years and over ( n = 1500). Results: Apart from voting in regional elections – which most of the respondents believed to be an influential way to make improvements in healthcare (74%) – respondents believed more in individual patient activities than activities associated with adopting a citizen role and acting collectively. A majority of respondents believed in the impact of replying to patient surveys (67%), making a complaint (61%), talking directly to staff (58%) or changing their healthcare provider (54%). Fewer believed in the impact of joining a patient organization (46%), taking part in a citizen council (35%) or joining a political party (34%). Beliefs in impact increased with educational attainment and decreased with age. Conclusions: The results suggest people have more confidence in the impact of participating as individual patients rather than collectively and as citizens. To ensure that activities enable 'participation and influence in society', complementary opportunities for collective involvement that also take into account under-represented voices such as those with a low level of education need to be developed.